2009
DOI: 10.1186/1532-429x-11-11
|View full text |Cite
|
Sign up to set email alerts
|

Cell tracking and therapy evaluation of bone marrow monocytes and stromal cells using SPECT and CMR in a canine model of myocardial infarction

Abstract: Background: The clinical application of stem cell therapy for myocardial infarction will require the development of methods to monitor treatment and pre-clinical assessment in a large animal model, to determine its effectiveness and the optimum cell population, route of delivery, timing, and flow milieu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Given this and some ethical considerations as to potential adverse effects of GFP-modified cells, its use was considered inappropriate for cell tracking in client-owned dogs. Instead, we used PKH26 red fluorescent dye, a lipophilic cell membrane stain that has previously been used for tracking of a variety of different cell types (Wisenberg et al, 2009). Data in the present study showed that cell viability and population doubling time of MSCs in culture was not significantly affected by PKH26 staining, corroborating findings of a previously reported study in which no effect on cell growth or proliferation was observed (Shao-Fang et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Given this and some ethical considerations as to potential adverse effects of GFP-modified cells, its use was considered inappropriate for cell tracking in client-owned dogs. Instead, we used PKH26 red fluorescent dye, a lipophilic cell membrane stain that has previously been used for tracking of a variety of different cell types (Wisenberg et al, 2009). Data in the present study showed that cell viability and population doubling time of MSCs in culture was not significantly affected by PKH26 staining, corroborating findings of a previously reported study in which no effect on cell growth or proliferation was observed (Shao-Fang et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…As in other cardiac MRE studies [4,12,13], we did not exclude the blood pool from our analysis. The rationale behind this is that wall vibration is transmitted into a confined fluid by pressure or nonevanescent waves (see e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Assessing MO on EGE requires a fixed, high inversion-time (TI) and is generally performed at ~2-4 min following contrast administration (Figure 6). With the recent advent of accelerated high-resolution perfusion sequences (1.5 mm × 1.5 mm spatial resolution, 8 slices acquired over 2 R-R intervals) [21], it is now possible to detect true first pass MO and quantify it for the entire LV (Figure 6). …”
Section: Reviewmentioning
confidence: 99%